2015
DOI: 10.1149/2.0521507jes
|View full text |Cite
|
Sign up to set email alerts
|

Ionicity Analysis of Silylamine-Type Reversible Ionic Liquids as a Model Switchable Electrolyte

Abstract: Separation of the electrochemical product from an electrolyte can add challenges to the overall process. Use of a switchable electrolyte offers the possibility to reduce or eliminate these separation challenges while maintaining high conductivity. Reversible ionic liquids (RevILs) are a type of switchable solvent that could be used as a switchable electrolyte. Switchable solvents are solvents that can have dramatic step-changes in their properties with the introduction of an external stimulus, in this case CO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…5,[9][10][11][12][13] We previously reported on the feasibility of using silylaminetype RevILs as an electrolyte by studying the ionicity and electrochemical window of commercially-available (3-aminopropyl) triethoxysilane (TEtoxySA) neat and when mixed with solvents. 8 We found that both the neat TEtoxySA RevIL and ML states had negligible conductivity. When the TEtoxySA-RevIL state was combined with high dielectric constant solvents (polar protic or polar aprotic), conductivities up to three orders of magnitude higher than the TEtoxySA-ML in solvent were observed, illustrating the possibility of TEtoxySA being used as a switchable electrolyte.…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…5,[9][10][11][12][13] We previously reported on the feasibility of using silylaminetype RevILs as an electrolyte by studying the ionicity and electrochemical window of commercially-available (3-aminopropyl) triethoxysilane (TEtoxySA) neat and when mixed with solvents. 8 We found that both the neat TEtoxySA RevIL and ML states had negligible conductivity. When the TEtoxySA-RevIL state was combined with high dielectric constant solvents (polar protic or polar aprotic), conductivities up to three orders of magnitude higher than the TEtoxySA-ML in solvent were observed, illustrating the possibility of TEtoxySA being used as a switchable electrolyte.…”
mentioning
confidence: 66%
“…Transferability of TEtoxySA findings to TEtSA.-While a baseline understanding of TEtoxySA-RevIL/solvent as an electrolyte has previously been established, 8 there was a need to determine if the more stable (3-aminopropyl)trialkylsilanes behaved similarly as an electrolyte. TEtSA, an analog to the TEtoxySA with the ether linker removed, was used to make the preliminary comparisons.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations